Effects of sacubitril/valsartan on the functional capacity of real-world patients in Italy: the REAL.IT study on heart failure with reduced ejection fraction - Sarullo, Filippo Maria; Nugara, Cinzia; Sarullo, Silvia; Iacoviello, Massimo; Di Gesaro, Gabriele; Miani, Daniela; Driussi, Mauro; Correale, Michele; Bilato, Claudio; Passantino, Andrea; Carluccio, Erberto; Villani, Alessandra; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background. Heart failure (HF) significantly affects morbidity, mortality, and quality of life of patients. New therapeutic strategies aim to improve patients' functional capacity and quality of life while controlling HF-related risks. Real-world data on both functional and cardiopulmonary exercise capacity in patients with HFrEF upon sacubitril/valsartan use are lacking. Methods. The multicenter, retrospective, cohort study REAL.IT was performed on the basis of data collected from the electronic medical records of the nine specialized heart failure centers in Italy. Cardiopulmonary exercise test was performed at baseline and after 12 months of sacubitril/valsartan therapy, monitoring carbon dioxide production (VCO2) and oxygen consumption (VO2). Results. Functional capacity was evaluated in 170 patients. The most common comorbidities were hypertension and diabetes (53.5% and 32.4%, respectively). At follow-up, both VO2 peak (from 15.1 ± 3.7 mL/kg/min at baseline to 17.6 ± 4.7 mL/kg/min at follow-up, p<0.0001) and predicted % VO2 peak (from 55.5 ± 14.1 to 65.5 ± 16.9, p<0.0001) significantly increased from baseline. VO2 at anaerobic threshold (AT-VO2) increased from 11.5 ± 2.6 to 12.5 ± 3.3 mL/kg/min (p = 0.021), and the rate ratio between oxygen uptake and change in work (ΔVO2/Δwork slope) improved from 9.1 ± 1.5 to 9.9 ± 1.6 mL/min/W (p<0.0001). Conclusions. Sacubitril/valsartan allows an improvement of cardiopulmonary capacity in patients with HFrEF in daily clinical practice in Italy.